Adverse Effects of Tannin Contained in Mimosa pudica Root Extract - Jaya Vejayan, Palliah (Asian Network for Scientific Information, 2016)
Background and Objective: Mimosa pudica has been used for many traditional healings including snake bites, wound healing, treating bleeding piles, ulcers, diarrhea, anti-inflammatory, anti-diabetic, anti-oxidant and anti-microbial etc. Tannin extracted from plants been beneficial as therapeutics with dividing opinions on its safety. Hence, this study investigated the safety of the total tannin extracted from the root of Mimosa pudica plant. Methodology: This investigation utilized biochemical markers as well as cytotoxicity and histopatological experiments. Additionally, the total condensed and hydrolysable tannins determined in the particular root extract of the Mimosa pudica plant. Results: Extract of MPT at the highest dose tested 2.5 mg mL–1 elevated significantly the levels of mice serum contained ALT and AST while no observable changes to ALP and GGT levels detected. The cytotoxicity of MPT was found to be with CTC50 values of 0.0653 and 0.119 mg mL–1 in vero and MDCK cell lines, respectively. The mice organ’s histopathology of liver and kidney demonstrated MPT having distinct toxic effects at the highest concentration tested. The total tannin in MPT found to be 3.28 mg TAE g–1 dry weight with more hydrolysable type of tannin than condensed tannin 0.31 TAE/dry weight. Conclusion: The MPT found to show adverse effects in all experiments conducted at the highest concentration of 2.5 mg mL–1. Hence, the age old doubt regarding the adverse effects of tannin being proven here whereby it was discovered the use of Mimosa pudica total tannin is concentration dependent. Therefore, warranted prior caution in determining the safe levels of tannin required before usage.